A Novel Method Based on Biogeography-Based Optimization for DG Planning in Distribution System - Mohammad Sedaghat; Esmaeel Rokrok; Mohammad Bakhshipour (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper proposed a novel technique based on biogeography-based optimization (BBO) algorithm in order to optimal placement and sizing of distinct types of Distributed Generation (DG) units in the distribution networks which is applied to improve voltage profile as the main factor for power quality improvement and reduce power losses. In order to promote the investigation to be capable in practical terms, the loads are linearly varied in small steps of 1% from 50% to 150% of the base value. The optimal size and location of distinct types of DGs are found out in each load step. This will aid the distribution network operators (DNOs) to have a long term scheduling for the optimal management of DG units and achieve the maximum performance. To verify the efficiency of proposed method, it has been conducted to IEEE 33-bus radial distribution system. Also, simulation results are compared with the analytical approach and HPSO algorithm (mixed binary and typical particle swarm optimization algorithm). The obtained simulation results demonstrate the better performance and effectiveness of the proposed method. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.8083